Laju Pendinginan Coolant Ethylene Glycol Pada Mesin Pendingin Type Chiller Untuk Cold Storage - Hendrik Syahputra; Azridjal Aziz; Rahmat Iman Mainil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Refrigeration a necessity in life today's, especially for urban communities. Refrigeration can be in domesticrefrigerators, cold storage, refrigeration of vegetables, fruits, meat, drinks and so on. Vapor compression refrigerationsystem also used in HVAC applications. The aim of this refrigerating cools machine the coolant ethylene glycol so thatthe temperature is below 0°C for cold storage. Coolant ethylene glycol functions as a heat absorber that in cold storage,cold storage cooling at a rate influenced by temperature changes in and out in the cold storage, the greater the heatabsorbed by the coolant ethylene glycol, the greater the cooling rate.Keywords: Cooling machine, cold storage, coolant ethylene glycol, refrigerant